2014
DOI: 10.4103/0019-509x.175371
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of KRAS mutations in metastatic colorectal cancer: A retrospective observational study from India

Abstract: The results suggest a prevalence of KRAS mutation at 42.8% in Indian population indicating that this testing is very crucial for targeted therapy management in metastatic CRC in India. Further analysis on mutation status of other homologues such as NRAS and downstream partner, v-raf murine sarcoma viral oncogene homolog B1, would add value to understanding the role of anti-epidermal growth factor receptor therapy in CRC management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
7
8
1
Order By: Relevance
“…Similar to the findings in the Indian study reported by Veldore et al [7], no significant correlation was found between the KRAS genotypes and the patients’ age and gender in this study. However, significantly higher mutation rates in well-differentiated tumours and tumours located at the distal end of the colon were observed in the Indian cohort.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to the findings in the Indian study reported by Veldore et al [7], no significant correlation was found between the KRAS genotypes and the patients’ age and gender in this study. However, significantly higher mutation rates in well-differentiated tumours and tumours located at the distal end of the colon were observed in the Indian cohort.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to these studies, the most common mutation identified in codon 12 in this study was p.Gly12Val (24.0%). A similar finding was observed in a retrospective study conducted among 299 patients with mCRC in India [7]. This may be a reflection of the genetic heterogeneity in the pattern of KRAS mutations in mCRC patients.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…When it comes to tumor location, disparities have been reported where KRAS mutation rates were higher in the right-sided CRC tumors [2,36,40,44]. Our study, along with others, showed an association rather with the left side of the colon [45][46][47][48].…”
Section: Discussionsupporting
confidence: 59%